PERENCANAAN PENERAPAN CONSTRUCTED WETLAND UNTUK PENGOLAHAN EFLUEN TANGKI SEPTIK - Soeprijanto Soeprijanto (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2008)
Wetlands are natural wet ecosystems with diverse and complex roles in nature and fundamentally wetlands are at least intermittently flooded with water depths that support the growth of emergent vegetation such as cattail, reeds, sedges, bulrushes, rushes, and grasess. The vegetation provides surfaces for the attachment of microbial films, aids on filtration and adsorption of wastewater constituents, transfer oxygen into the water column, and controls the growths of algae by restricting the penetration of sunlight. The extensive root systems serve as large surface areas for the development of microorganisms and enabling filtration as well as adsorption of sediment. Design of the system consisted of two wetland cells in series, namely the subsurface flow (SSF) and the free water surface (FWS) cells. The SSF had an effluent rate of 8 m3/day, surface area of 35,68 m2, bed width of 3,6 m, length of 10 m, depth of 0,6 m, cross sectional area of 2,16 m2, organic loading rate (OLR) of 179,37 kg BOD/ha-day, HLR of 0,2242 m3/m2-day, and residence time of 1 day. The FWS had a surface area of 19,71 m2, bed width of 2,5 m, length of 8 m, depth of 0,3 m, cross sectional area of 0,75 m2, OLR of 83,21 kg BOD/ha-day, HLR of 0,4059 m3/m2-day, and residence time of 1 day.